IMAGINER 2—improving accuracy with augmented realIty navigation system during placement of external ventricular drains over Kaufman's, Keen's, Kocher's and Frazier's point - Vychopen, Martin; Kropla, Fabian; Winkler, Dirk; Güresir, Erdem; Grunert, Ronny; Wach, Johannes (Frontiers in Surgery, 2025)
BackgroundExternal ventricular drain (EVD) placement is a routine neurosurgical procedure used to treat acute hydrocephalus and monitor intracranial pressure. Kocher's point is the most commonly used anatomical landmark, but other entry points can be challenging even for experienced neurosurgeons. Augmented reality (AR) may enhance the accuracy and safety of these procedures. Previous studies demonstrated improved ventriculostomy accuracy using AR among novices. This study evaluates AR's impact on EVD placement accuracy performed by experienced neurosurgeons.MethodsEighteen neurosurgical experts performed ventriculostomies on a Styrofoam head model using Kaufman's, Keen's, Kocher's, and Frazier's points. Punctures were performed freehand (Freehand group) and with AR assistance (AR group). Post-procedure CT scans were used to compare the actual catheter tip positions with the ideal positions. Accuracy was assessed by the distance between real and ideal catheter tips and by Kakarla grading.ResultsThe AR group had a mean tip distance of 16.93 ± 9.38 mm compared to 21.71 ± 9.69 mm in the Freehand group (p = 0.003). The AR group also showed better Kakarla grading outcomes (Grade 1: n = 26, Grade 3: n = 26) vs. the Freehand group (Grade 1: n = 7, Grade 3: n = 53; p < 0.0001). Neurosurgeons with ≥7 years of experience demonstrated higher accuracy across both methods (p = 0.040).ConclusionAR significantly enhances the accuracy of EVD placement, particularly using Kaufman's, Keen's, Kocher's, and Frazier's points, with experienced neurosurgeons benefiting the most from AR assistance.